Natural tissue concentrations in adult Ambystoma maculatum and larval DNA damage from exposure to arsenic and chromium. Issue 12 (18th June 2018) - Gardner, Steven; Cline, George; Mwebi, Nixon; Rayburn, James
ABSTRACT: Arsenic (As) and chromium (Cr) are two contaminants that are detected in aquatic and terrestrial habitats. Using the spotted salamander, Ambystoma maculatum, to assess impacts from these contaminants may be advantageous as adults live and breed in such environments. Adult amphibians typically exhibit elevated tissue concentrations of contaminants present in their environment, while larval stages were found to exhibit increased sensitivity to pollutants. From January through March of 2015, during the spring breeding season, 5 adults and approximately 32 egg masses were collected from a local breeding site. Field levels of As and Cr ranged from 5.99 to 8.88 µg/L and 1.45 to 2 µg/L, respectively, while mean adult As tissue concentrations were 56.74 µg/g dry weight for heart, 0.92 µg/g for liver, and 1.21 µg/g for tail tissue. Mean tissue concentrations for Cr were 87.64 µg/g for heart, 1.47 µg/g for liver, and 6.92 µg/g for tail. Developing larvae that were collected from the field and exposed in a lab setting for 12 d to 0.2 or 20 mg/L of either As or Cr displayed little DNA damage attributed to As, but marked damage due to exposure to 20 mg/L Cr when assessed using the comet assay. Exposure to a mixture of either 0.25:0.1 or 25:10 mg/L As and Cr resulted in significant DNA damage at the lower concentration of 0.25:0.1 mg/L. As adult spotted salamanders were found to possess high concentrations of these contaminants in cardiac tissue, and larvae were shown to be susceptible to DNA damage from increased exposures, assessing impacts and potential declines of amphibian populations exposed to As and Cr is needed.